2022
DOI: 10.1371/journal.pone.0262881
|View full text |Cite
|
Sign up to set email alerts
|

Community monitoring of coliform pollution in Lake Tanganyika

Abstract: Conventional water quality monitoring has been done for decades in Lake Tanganyika, under different national and international programs. However, these projects utilized monitoring approaches, which were temporally limited, labour intensive and costly. This study examines the use of citizen science to monitor the dynamics of coliform concentrations in Lake Tanganyika as a complementary method to statutory and project-focused measurements. Persons in five coastal communities (Kibirizi, Ilagala, Karago, Ujiji an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…3.1 Bacteriological Properties: Presence of bacteria in drinking water considers one of the important indicators to identify the degree of contamination of all water sources with aerobic, facultative and nonaerobic bacteria and it was bioindicator for organic pollution [18] [19].…”
Section: Resultsmentioning
confidence: 99%
“…3.1 Bacteriological Properties: Presence of bacteria in drinking water considers one of the important indicators to identify the degree of contamination of all water sources with aerobic, facultative and nonaerobic bacteria and it was bioindicator for organic pollution [18] [19].…”
Section: Resultsmentioning
confidence: 99%
“…Turbidity is expected to decrease exponentially with distance from the river mouth in deep lakes (Giovanoli, 1990 ). The catchments of rivers are characterised by a range of anthropogenic activities (Moshi et al, 2022 ). Conversely, Gombe is located in a protected area and is surrounded by forest with only limited agricultural activities.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring has successfully been done in open waters to explore changes in water quality (Azanga, 2016 ; Bergamino et al, 2010 ; Cohen et al, 2005 ; Gao et al, 2018 ; Kalacska et al, 2017 ; Karamage et al, 2016 ; Mziray et al, 2018 ). However, limited monitoring has been done along the shoreline, where major inputs occur (Moshi et al, 2022 ). Although remote sensing and laboratory techniques offer potential, these approaches are expensive and require trained technical staff for sampling and analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that surface runoff, even after light rainfall (<2.5 mm of rain) is major driver which contributing diffuse pollution both in surface and bottom waters in the pond. This result is consistent with previous studies reported positive correlation between coliform bacteria and rainfall events at lake and pond ecosystems (An et al, 2002;Jeon et al, 2019;Moshi et al, 2022;Ramos-Ramírez et al, 2020;Staley et al, 2012;Staley et al, 2013;Stocker et al, 2019;Tryland et al, 2011;Xue et al, 2018). On the other hand, few studies reported no significant relationship between fecal indicator bacteria and rainfall (Nguyen et al, 2016;Sampson et al, 2006).…”
Section: Spatiotemporal Variability Of Physicochemical Parameters And...mentioning
confidence: 93%